Volume 8: Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2016
DOI: 10.1115/gt2016-57190
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cross Flow in Double Entry Turbocharger Turbines

Abstract: The downsizing of combustion engines has become the major strategy within the automotive industry to meet the increasing demands in terms of fuel economy and harmful emissions. Furthermore, it is important to fulfil the customers expectations in terms of drivability by increasing the power density and transient performance of the engines. The key technology to reach these ambitious targets is the enhanced utilization of exhaust pulses on turbocharged engines. In four cylinder gasoline engine applications this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…25 In addition, the degree of complexity is increased in fully unsteady turbine models, and performance could be poorly predicted under unequal flow admissions for twin- and double-entry turbocharger turbines. 26 Whereas extended mapping of twin- and double-entry turbocharger turbines is able to capture unsteady performance, 27 a quasi-steady assumption for the turbine rotor could be able to model turbocharger turbine behaviour. 28…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, the degree of complexity is increased in fully unsteady turbine models, and performance could be poorly predicted under unequal flow admissions for twin- and double-entry turbocharger turbines. 26 Whereas extended mapping of twin- and double-entry turbocharger turbines is able to capture unsteady performance, 27 a quasi-steady assumption for the turbine rotor could be able to model turbocharger turbine behaviour. 28…”
Section: Introductionmentioning
confidence: 99%
“…Few authors [33,34,35] suggested that, if twin-entry and dual-volute turbines are modelled as in the view of two turbine approach (TTA) attached to a single compressor, then the effective turbine efficiency can be calculated as the ratio between the compressor power to the sum of two individual isentropic turbine powers of the individual turbine flows; as shown in the Equation 2. 13.…”
Section: Turbine Performance Datamentioning
confidence: 99%
“…The rotor outlet geometrical area (A geom ) is calculated by taking the arithmetic diameter between the turbine rotor shroud (D 4 ) and rotor hub (D nut ) diameters as shown in Equation 2. 33.…”
Section: Mass Flow Modelmentioning
confidence: 99%
See 1 more Smart Citation